Prevention of acute renal injury and drug modification - Amita Kaul; Sachin Shah (Wolters Kluwer Medknow Publications, 2018)
Acute kidney injury (AKI) causes increased morbidity in critically ill children and damage to the kidney affects survival. The incidence of AKI in pediatrics is significant and despite alarming data, therapeutic interventions have failed to effect a meaningful difference in outcomes. In this review, we will discuss prevention of AKI in paediatrics, drug modification, need for risk stratification and staging which would help to recognise at risk children.